Огляд транспортних протоколів онлайн трансляцій - Вяткіна, В. О. (ХНУРЕ, 2023)
This article discusses transport protocols in detail, as they are an integral part of online broadcasts, as they provide a stable connection between the server and the viewer's device, which allows video and audio to be transmitted without delays and loss of quality.
Keywords: протокол онлайн трансляцій